1983
DOI: 10.1161/01.atv.3.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced macrophage degradation of biologically modified low density lipoprotein.

Abstract: Low density lipoprotein (LDL) conditioned by incubation in the presence of rabbit aortic or human umbilical vein endothelial cells (endothelial cell-modified LDL) was degraded by macrophages three to five times more rapidly than LDL incubated in the absence of cells (control LDL). This enhanced degradation occurred mostly via a high affinity, saturable pathway related to the pathway for macrophage uptake of acetylated LDL. Conditioning LDL with cultured aortic smooth muscle cells had a qualitatively similar bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
188
0
3

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 448 publications
(195 citation statements)
references
References 28 publications
(29 reference statements)
4
188
0
3
Order By: Relevance
“…Our results show that incubation of LDL in serum-free medium with human umbilical vein EC or bovine aortic SMC, but not human fibroblasts or bovine aortic EC, resulted in a modified LDL with increased electrophoretic mobility. These findings are in general agreement with the results of Henriksen et al 8 " 10 Like these authors, 10 we observed that the electrophoretic mobility change was accompanied by a variable decrease in the LDL sterol. A decreased total cholesterol/protein ratio of up to 20% was observed after 48 hours of incubation of LDL with human umbilical vein EC or bovine SMC.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our results show that incubation of LDL in serum-free medium with human umbilical vein EC or bovine aortic SMC, but not human fibroblasts or bovine aortic EC, resulted in a modified LDL with increased electrophoretic mobility. These findings are in general agreement with the results of Henriksen et al 8 " 10 Like these authors, 10 we observed that the electrophoretic mobility change was accompanied by a variable decrease in the LDL sterol. A decreased total cholesterol/protein ratio of up to 20% was observed after 48 hours of incubation of LDL with human umbilical vein EC or bovine SMC.…”
Section: Resultssupporting
confidence: 93%
“…The purpose of the spin was to reisolate LDL. A solvent density of 1.100 was used to collect LDL that might have increased in density as indicated by Henriksen, et al 9 ' 10 The reisolated LDL was then assayed for cholesterol, protein, TBARS, electrophoretic mobility, and cytotoxicity.…”
Section: Reisolation Of Ldlmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated in vitro, however, that LDL can be oxidised by the main cells present in atherosclerotic lesions, namely endothelial cells [3], smooth muscle cells [4], monocyte-macrophages [5 7] and lymphocytes [8]. Most workers find that LDL oxidation by cells requires the presence of transition metal ions, usually iron [7,9], but copper ions will also catalyse the oxidation [9,10].…”
Section: Reagentsmentioning
confidence: 99%